ANALISIS KETERSEDIAAN MEDIA PEMBELAJARAN TERHADAP HASIL BELAJAR SISWA KELAS IV SEKOLAH DASAR - Hen'st Valen Adip Benu; Maria Anjelina Pete; Kesya Igelda Missa; Marfin Ajilo Kase; Maria Diana Lite; Habibi Musa; Adam Bol Nifu Benu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
still unreliable and not used consistently in the learning process. This situation has the potential to hinder the media's ability to maximize student understanding of content and learning outcomes. Based on this phenomenon, this study aims to analyze the availability of educational media and its contribution to the learning outcomes of grade IV C students at SDI Oesapa Kecil 1. The method used is a quantitative descriptive approach with a survey methodology applied to 25 students and one teacher in grade IV C. Descriptive statistics were used in data analysis to describe trends in the areas of availability, ease of use, media suitability to content, and student reactions to media use. The study findings indicate that educational media are widely available, easy to use, and able to improve students' understanding of the subject matter and increase their learning motivation. Positive statements are included in the high category, while negative statements are included in the low category, indicating little difficulty in using the media. The mentioned teachers also provided very positive feedback regarding all aspects of educational media. In general, the availability and use of media have a positive impact on the learning outcomes of grade IV C students.